DNA Computing: Principle, Construction, and Applications in Intelligent Diagnostics. Issue 11 (12th November 2021) - Ma, Qian; Zhang, Chao; Zhang, Mingzhi; Han, Da; Tan, Weihong
Abstract : DNA Computing DNA computing can integrate the functions of nucleic acids as biomolecules that recognize biomarkers with their ability to analyze and perform computational functions. In article number 2100051 by Da Han, Weihong Tan, and co‐workers, the most recent and important developments in DNA‐based computing for biomedical applications are presented, mainly from the perspective of biosensing related to diagnostics. Design and implementation of DNA computing systems from all stages in the pipeline are also discussed.